Positive electrode material, positive electrode plate, preparation method of positive electrode plate and solid-state battery
By coating the surface of the positive electrode active material of the solid-state battery with an organic-inorganic composite coating layer, the problem of unstable solid-solid contact interface in the solid-state battery is solved, and the battery's cycle performance and energy density are improved.
Patent Information
- Application Number
- CN202510603853.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-09-12
AI Technical Summary
The lack of liquid electrolyte wetting on the electrodes in solid-state batteries leads to unstable solid-solid contact interface, affecting the battery's cycle performance and energy density.
A composite coating layer of organic polymer and inorganic solid electrolyte is coated on the surface of the positive electrode active material to form a continuous membrane structure, thereby improving interface stability and lithium ion transmission efficiency.
It enhances the interfacial stability of solid-state batteries, reduces the chemical and electrochemical reaction rates, and improves the battery's cycle performance and energy density.
Smart Images

Figure CN120637416A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode material, a positive electrode plate and a preparation method thereof, and a solid-state battery. Background Art
[0002] In the design of solid-state batteries, by replacing the separator and electrolyte with a solid electrolyte and using high-energy-density metal lithium or silicon-carbon as the negative electrode material, the energy density of solid-state batteries can be significantly improved, making solid-state batteries show obvious advantages in providing longer battery life. However, the lack of liquid electrolyte infiltration into the pores in the electrode poses a challenge to the solid-solid contact interface in solid-state batteries. Summary of the Invention
[0003] The embodiments of the present application provide a positive electrode material, a positive electrode plate and a preparation method thereof, and a solid-state battery to improve the stability of the solid-solid contact interface in the solid-state battery.
[0004] In a first aspect, an embodiment of the present application provides a positive electrode material, comprising a positive electrode active substance and a coating layer coated on the surface of the positive electrode active substance, wherein the coating layer comprises an organic polymer and an inorganic solid electrolyte dispersed in the organic polymer.
[0005] In one embodiment, the positive electrode active material includes at least one of a nickel-cobalt-manganese ternary material and a nickel-cobalt-aluminum ternary material.
[0006] In one embodiment, the inorganic solid electrolyte includes an oxide solid electrolyte, and the oxide solid electrolyte contains at least one of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, and tantalum-doped lithium lanthanum zirconium oxide.
[0007] In one embodiment, the organic polymer is polymerized from at least one of the following organic monomers: vinylene carbonate, vinyl ethylene carbonate, styrene, ethylene glycol, acrylic acid, acrylonitrile, methyl methacrylate, methyl acrylate ketone, lauric acid, butyl acrylate, and dioxolane.
[0008] In one embodiment, the coating layer has a thickness of 8 nm to 20 nm.
[0009] In one embodiment, the inorganic solid electrolyte is nanoscale inorganic solid electrolyte particles.
[0010] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising:
[0011] Providing a first mixed material, wherein the first mixed material includes a positive electrode active material and an initiator attached to a surface of the positive electrode active material;
[0012] Providing a coating slurry, wherein the coating slurry includes a liquid organic monomer and an inorganic solid electrolyte dispersed in the organic monomer;
[0013] The first mixed material is dispersed in the coating slurry, and the organic monomer undergoes a polymerization reaction under the action of the initiator to generate an organic polymer. The organic polymer and the inorganic solid electrolyte adhere to the surface of the positive electrode active material and form a coating layer, thereby obtaining a positive electrode material.
[0014] In one embodiment, the positive electrode active material includes at least one of a nickel-cobalt-manganese ternary material and a nickel-cobalt-aluminum ternary material.
[0015] In one embodiment, the initiator includes an alkaline substance, and in the first mixture, the content of the alkaline substance on the surface of the positive electrode active material is less than or equal to 9000 ppm.
[0016] In one embodiment, the inorganic solid electrolyte includes an oxide solid electrolyte, and the oxide solid electrolyte contains at least one of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, and tantalum-doped lithium lanthanum zirconium oxide.
[0017] In one embodiment, the organic monomer includes at least one of vinylene carbonate, vinyl ethylene carbonate, styrene, ethylene glycol, acrylic acid, acrylonitrile, methyl methacrylate, methyl acrylate ketone, lauric acid, butyl acrylate, and dioxolane.
[0018] In one embodiment, the content of the inorganic solid electrolyte in the coating slurry is 0.5 wt % to 10 wt %.
[0019] In one embodiment, the inorganic solid electrolyte is nanoscale inorganic solid electrolyte particles.
[0020] In one embodiment, the coating slurry further comprises a dispersant, and the dispersant comprises at least one of polyethylene glycol, polypropylene glycol, octylphenol polyoxyethylene ether, polysorbate monooleate, and polyvinyl pyrrolidone.
[0021] In one embodiment, the reaction conditions of the polymerization reaction include: stirring at a first temperature for a first time, the first temperature is 25° C. to 80° C., and the first time is 2 h to 72 h.
[0022] In one embodiment, dispersing the first mixture in the coating slurry includes: mixing the first mixture and the coating slurry in a mass ratio of (20-55): (45-80) to obtain a mixed slurry, and then adding the organic monomer to adjust the solid content of the mixed slurry to 20wt% to 60wt%.
[0023] In one embodiment, before obtaining the positive electrode material, the method for preparing the positive electrode material further comprises: filtering, washing, drying and grinding the product of the polymerization reaction.
[0024] In a third aspect, an embodiment of the present application provides a positive electrode sheet, comprising a current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode material as described above or the positive electrode material prepared by the method for preparing the positive electrode material as described above.
[0025] In one embodiment, the positive electrode active material layer further includes a binder, and the binder includes polytetrafluoroethylene.
[0026] In one embodiment, the positive electrode active material layer further includes a conductive agent.
[0027] In a fourth aspect, an embodiment of the present application provides a method for preparing a positive electrode sheet, comprising:
[0028] Providing a dry material, wherein the dry material includes a positive electrode material, and the positive electrode material is the positive electrode material as described above or a positive electrode material prepared by the method for preparing the positive electrode material as described above;
[0029] The dry material is sequentially subjected to stirring and roller pressing to obtain a positive electrode active material layer;
[0030] The positive electrode active material layer is pressed onto the surface of the current collector to obtain a positive electrode sheet.
[0031] In fifth aspect, an embodiment of the present application provides a solid-state battery, comprising a positive electrode sheet, a negative electrode sheet, and a solid electrolyte membrane arranged between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet as described above or the positive electrode sheet prepared by the preparation method of the positive electrode sheet as described above.
[0032] Beneficial effects of the embodiments of the present application:
[0033] The positive electrode material provided in the embodiments of the present application can be applied to solid-state batteries. The surface of the positive electrode active material is modified by adopting an interface modification technology. Specifically, a surface coating layer of the positive electrode active material is formed, and the coating layer contains an inorganic solid electrolyte and an organic polymer. The organic polymer has a chain molecular structure, and the organic polymer molecules are easily entangled to form a network structure. In this way, the coating layer can be formed into a continuous film structure coated on the surface of the positive electrode active material, and the inorganic solid electrolyte with high ionic conductivity is dispersed in the organic polymer. On the one hand, the organic polymer enables the inorganic solid electrolyte to form good contact with the positive electrode active material. On the other hand, the inorganic solid electrolyte can also construct a "high-speed channel" for lithium ion transport in the organic polymer. In this way, during the charging and discharging process of the solid-state battery, the coating layer can effectively transmit lithium ions while reducing the interface chemical and electrochemical reaction rates and inhibiting the occurrence of interface side reactions. In addition, the organic polymer in the coating layer can give the coating layer a certain buffering and strain absorption ability, thereby reducing the adverse effects of the volume change of the interface material during the charging and discharging process of the solid-state battery. Compared with the inorganic coating layer or organic coating layer of a single material, the coating layer in the embodiment of the present application is an organic-inorganic composite coating layer, which not only has good deformation ability, but also has the ability to reduce the interface chemical and electrochemical reaction rates. In this way, during the charging and discharging process of the solid-state battery, the positive electrode material can simultaneously take into account the requirements of the multi-physical field synergistic effect of the solid-state battery positive electrode interface, improve the stability of the solid-solid contact interface in the solid-state battery, and thus improve the cycle performance of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 is a scanning electron microscope (SEM) image of the high nickel positive electrode active material before coating in Example 1 of the present application;
[0036] Figure 2 is a scanning electron microscope (SEM) image of the coated high nickel positive electrode active material in Example 1 of the present application;
[0037] Figure 3 This is the thermogravimetric analysis (TGA) spectrum of the positive electrode materials finally prepared in Example 2, Example 5 and Example 7 of the present application;
[0038] Figure 4It is a Fourier transform infrared spectrum (FT-IR) graph of the coating layer in the positive electrode material finally prepared in Example 2, Example 4, Example 6, Example 8 and Example 10 of the present application. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the embodiments described are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without making creative efforts are within the scope of protection of this application.
[0040] Furthermore, it should be understood that the specific embodiments described herein are intended only to illustrate and explain the present application and are not intended to limit the present application. In this application, unless otherwise indicated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of a unit in actual use or operation, specifically the directions of the drawings in the accompanying drawings; whereas "inner" and "outer" refer to the outline of a unit.
[0041] The terms "first" and "second" are used for descriptive purposes only and should not be understood to indicate or imply relative importance or implicitly specify the number of the technical features indicated. Therefore, a feature specified as "first" or "second" may explicitly or implicitly include one or more of the specified features. In the description of this application, "plurality" means two or more, unless otherwise specifically specified.
[0042] In the description of this application, it should be noted that, unless otherwise expressly specified or limited, the terms "installed," "connected," and "connected" should be understood in a broad sense. For example, they can refer to fixed connections, detachable connections, or integral connections; they can refer to mechanical connections, electrical connections, or mutual communication; they can refer to direct connections or indirect connections through an intermediate medium; they can refer to internal communication between two components or the interaction between two components. Those skilled in the art will understand the specific meanings of the above terms in this application based on specific circumstances.
[0043] The terms "comprises," "includes," or any other variations thereof are intended to encompass non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus. In the absence of further limitations, an element defined by the phrase "comprising a..." does not preclude the presence of additional identical elements in the process, method, article, or apparatus that includes the element.
[0044] In the description of the embodiments of this application, words such as "example" or "for example" are used to indicate an example, illustration, or description. Any embodiment or design described as "for example" or "for example" in the embodiments of this application is not to be construed as being preferred or having more advantages than another embodiment or design. The use of words such as "example" or "for example" is intended to clearly present relative concepts.
[0045] To facilitate understanding of the solution of the present application, the spline curves and arrows used in the drawings are explained here: the components indicated by the spline curves without arrows are solid components, that is, components with solid structures; the components indicated by the spline curves with arrows are virtual components, that is, components without solid structures.
[0046] In a first aspect, an embodiment of the present application provides a positive electrode material, which includes a positive electrode active substance and a coating layer coated on the surface of the positive electrode active substance, wherein the coating layer includes an organic polymer and an inorganic solid electrolyte dispersed in the organic polymer.
[0047] Organic polymers refer to high molecular weight compounds formed by chemical polymerization of organic monomers. Organic polymers usually have a certain degree of flexibility.
[0048] A solid electrolyte refers to a solid substance that can conduct ions (such as lithium ions). An inorganic solid electrolyte refers to a solid electrolyte that is inorganic. Compared to polymer solid electrolytes, inorganic solid electrolytes have the advantages of high ionic conductivity and high chemical stability. Optionally, the inorganic solid electrolyte includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, and a halide solid electrolyte.
[0049] The coating layer contains an inorganic solid electrolyte and an organic polymer, specifically a mixture of the two, with the organic polymer serving as a base material and the inorganic solid electrolyte dispersed within the organic polymer. Because the inorganic solid electrolyte has high ionic conductivity, it can create lithium ion transport channels within the coating layer.
[0050] The positive electrode material provided in the embodiments of the present application can be applied to solid-state batteries. The surface of the positive electrode active material is modified by adopting an interface modification technology. Specifically, a surface coating layer of the positive electrode active material is formed, and the coating layer contains an inorganic solid electrolyte and an organic polymer. The organic polymer has a chain molecular structure, and the organic polymer molecules are easily entangled to form a network structure. In this way, the coating layer can be formed into a continuous film structure coated on the surface of the positive electrode active material, and the inorganic solid electrolyte with high ionic conductivity is dispersed in the organic polymer. On the one hand, the organic polymer enables the inorganic solid electrolyte to form good contact with the positive electrode active material. On the other hand, the inorganic solid electrolyte can also construct a "high-speed channel" for lithium ion transport in the organic polymer. In this way, during the charging and discharging process of the solid-state battery, the coating layer can effectively transmit lithium ions while reducing the interface chemical and electrochemical reaction rates and inhibiting the occurrence of interface side reactions. In addition, the organic polymer in the coating layer can give the coating layer a certain buffering and strain absorption ability, thereby reducing the adverse effects of the volume change of the interface material during the charging and discharging process of the solid-state battery. Compared with the inorganic coating layer or organic coating layer of a single material, the coating layer in the embodiment of the present application is an organic-inorganic composite coating layer, which not only has good deformation ability, but also has the ability to reduce the interface chemical and electrochemical reaction rates. In this way, during the charging and discharging process of the solid-state battery, the positive electrode material can simultaneously take into account the requirements of the multi-physical field synergistic effect of the solid-state battery positive electrode interface, improve the stability of the solid-solid contact interface in the solid-state battery, and thus improve the cycle performance of the solid-state battery.
[0051] In some embodiments, the positive electrode active material includes a nickel-cobalt-manganese ternary material (LiNi x Mn y Co z O2, NMC) and nickel-cobalt-aluminum ternary materials (LiNi x Co y Al z O2, NCA). Ternary materials have the advantages of high energy density, good cycle performance and rate performance, which are conducive to further improving the electrochemical performance of solid-state batteries. As an example, the positive electrode active material includes a nickel-cobalt-manganese ternary material, and the nickel-cobalt-manganese ternary material includes at least one of NCM523 (nickel: cobalt: manganese = 5:2:3), NCM622 (nickel: cobalt: manganese = 6:2:2) and NCM811 (nickel: cobalt: manganese = 8:1:1).
[0052] In some embodiments, the inorganic solid electrolyte includes an oxide solid electrolyte. The oxide solid electrolyte has advantages in electrochemical stability, thermal stability and mechanical strength, which is conducive to further improving the comprehensive performance of the solid-state battery. The oxide solid electrolyte includes at least one of lithium aluminum titanium phosphate (LATP), lithium lanthanum titanium oxide (LLTO), lithium lanthanum zirconium oxide (LLZO) and tantalum-doped lithium lanthanum zirconium oxide (LLZTO). LATP is a NASICON-type solid electrolyte. As an example, the chemical formula of LATP is Li 1.5 Al 0.5 Ti 1.5 (PO4)3 or Li 1.3 Al 0.3 Ti 1.7 (PO4)3. LLTO belongs to the perovskite structure. As an example, the chemical formula of LLTO is Li 0.5 La 0.5 TiO3. The crystal structure of LLZO is garnet structure, which is mainly composed of lithium (Li), lanthanum (La), zirconium (Zr) and oxygen (O). As an example, the chemical formula of LLZO is Li7La3Zr2O 12 LLZTO is a variant of LLZO doped with tantalum (Ta). By doping with tantalum, the density and ionic conductivity of the material can be further improved. As an example, the chemical formula of LLZTO is Li 6.4 La3Zr 1.4 Ta 0.6 O 12 ). LATP, LLTO, LLZO and LLZTO all have high ionic conductivity and good chemical stability, which are beneficial to improving the effect of lithium ion transmission in the coating layer.
[0053] In some embodiments, the organic polymer is polymerized from at least one of the following organic monomers: vinylene carbonate, vinyl ethylene carbonate, styrene, ethylene glycol, acrylic acid, acrylonitrile, methyl methacrylate, methyl acrylate, lauric acid, butyl acrylate, dioxolane. The above substances can be liquid at room temperature or when slightly heated, so these substances can not only participate in the polymerization reaction as raw materials, but also can be used as solvents to disperse inorganic solid electrolytes, which can reduce the risk of adverse effects caused by the introduction of other solvents. Optionally, dioxolane includes 1,3-dioxolane. It should be noted here that the organic polymer can be polymerized from a single organic monomer or a copolymer polymerized from two or more organic monomers.
[0054] In some embodiments, the coating layer has a thickness of 8 nm to 20 nm. A coating layer that is too thin may not be able to completely cover the positive electrode active material, while a coating layer that is too thick may be detrimental to ion transport and reduce the cycle performance of the solid-state battery. As an example, the thickness of the coating layer is 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, or 20 nm.
[0055] In some embodiments, the inorganic solid electrolyte is nanoscale inorganic solid electrolyte particles. Nanoscale inorganic solid electrolyte particles refer to inorganic solid electrolyte particles having a particle size of nanometers. Nanoscale inorganic solid electrolyte particles dispersed in an organic polymer can effectively construct abundant lithium ion channels, which is beneficial for improving the cycling performance of solid-state batteries.
[0056] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising:
[0057] S101, providing a first mixed material, the first mixed material including a positive electrode active material and an initiator attached to the surface of the positive electrode active material;
[0058] S102, providing a coating slurry, wherein the coating slurry includes a liquid organic monomer and an inorganic solid electrolyte dispersed in the organic monomer;
[0059] S103, dispersing the first mixed material in the coating slurry, and under the action of the initiator, the organic monomer undergoes a polymerization reaction to generate an organic polymer, and the organic polymer and the inorganic solid electrolyte adhere to the surface of the positive electrode active material and form a coating layer, thereby obtaining a positive electrode material.
[0060] The preparation method of the above-mentioned positive electrode material is a liquid phase method. By adopting the liquid phase method, the inorganic solid electrolyte is dispersed in the organic monomer. When the organic monomer is polymerized into an organic polymer, the organic polymer simultaneously fixes the inorganic solid electrolyte and forms a continuous film structure on the surface of the positive electrode active material, thereby forming a coating layer that covers the surface of the positive electrode active material. The coating layer is an organic-inorganic composite coating layer, which not only has good deformation ability, but also has the ability to reduce the rate of interfacial chemical and electrochemical reactions. In this way, the positive electrode material can simultaneously take into account the requirements of the multi-physical field synergistic effect of the positive electrode interface of the solid-state battery, enhance the stability of the solid-solid contact interface in the solid-state battery, and thus improve the cycle performance of the solid-state battery.
[0061] In some embodiments, in step S101, the positive electrode active material includes a nickel-cobalt-manganese ternary material (LiNi x Mn y Co z O2, NMC) and nickel-cobalt-aluminum ternary materials (LiNi x Coy Al z O2, NCA). Ternary materials have the advantages of high energy density, good cycle performance and rate performance, which are conducive to further improving the electrochemical performance of solid-state batteries. As an example, the positive electrode active material includes a nickel-cobalt-manganese ternary material, and the nickel-cobalt-manganese ternary material includes at least one of NCM523 (nickel: cobalt: manganese = 5:2:3), NCM622 (nickel: cobalt: manganese = 6:2:2) and NCM811 (nickel: cobalt: manganese = 8:1:1).
[0062] In some embodiments, in step S101, the initiator includes an alkaline substance. The initiator can decompose to produce free radicals that can be used to initiate chemical processes such as free radical polymerization, copolymerization, and crosslinking and curing reactions of monomers. The initiator includes an alkaline substance that adheres to the surface of the positive electrode active material. These alkaline substances can be byproducts formed during the preparation of the positive electrode active material, such as residual alkali, or they can be alkaline substances added through other processing steps. As an example, the alkaline substance includes lithium hydroxide.
[0063] In some embodiments, in step S101, in the first mixture, the content of alkaline substances on the surface of the positive electrode active material is less than or equal to 9000 ppm. Generally, the content of alkaline substances on the surface of the positive electrode active material should not be too high, otherwise the coating layer will be too thick, which is not conducive to the transmission of lithium ions; and too high a content of alkaline substances will lead to redundancy of alkaline substances, and alkaline substances are prone to cause interfacial side reactions. As an example, the content of alkaline substances on the surface of the positive electrode active material is 500 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm, 5000 ppm, 6000 ppm, 7000 ppm, 8000 ppm or 9000 ppm. Generally, 1 ppm is equal to 1 mg / kg. Here, the content of alkaline substances on the surface of the positive electrode active material refers to the ratio of the mass of the alkaline substance to the mass of the positive electrode active material. 1500 ppm means that 1500 mg of alkaline substances are distributed on the surface of 1 kg of positive electrode active material.
[0064] In some embodiments, in step S101, the content of alkaline substances on the surface of the positive electrode active material in the first mixture is 1500 ppm to 4500 ppm. Generally, if the content of alkaline substances on the surface of the positive electrode active material is too low, the polymerization effect of the organic monomer will be poor, thereby affecting the quality of the coating layer, while if the content of alkaline substances is too high, the coating layer will be too thick and the interface side reactions will increase.
[0065] In some embodiments, in step S102, the inorganic solid electrolyte includes an oxide solid electrolyte. The oxide solid electrolyte has advantages in electrochemical stability, thermal stability and mechanical strength, which is conducive to further improving the comprehensive performance of the solid-state battery. The oxide solid electrolyte includes at least one of lithium aluminum titanium phosphate (LATP), lithium lanthanum titanium oxide (LLTO), lithium lanthanum zirconium oxide (LLZO) and tantalum-doped lithium lanthanum zirconium oxide (LLZTO). LATP is a NASICON-type solid electrolyte. As an example, the chemical formula of LATP is Li 1.5 Al 0.5 Ti 1.5 (PO4)3 or Li 1.3 Al 0.3 Ti 1.7 (PO4)3. LLTO belongs to the perovskite structure. As an example, the chemical formula of LLTO is Li 0.5 La 0.5 TiO3. The crystal structure of LLZO is garnet structure, which is mainly composed of lithium (Li), lanthanum (La), zirconium (Zr) and oxygen (O). As an example, the chemical formula of LLZO is Li7La3Zr2O 12 LLZTO is a variant of LLZO doped with tantalum (Ta). By doping with tantalum, the density and ionic conductivity of the material can be further improved. As an example, the chemical formula of LLZTO is Li 6.4 La3Zr 1.4 Ta 0.6 O 12 ). LATP, LLTO, LLZO and LLZTO all have high ionic conductivity and good chemical stability, which are beneficial to improving the effect of lithium ion transmission in the coating layer.
[0066] In some embodiments, in step S102, the organic monomer includes at least one of vinylene carbonate, vinyl ethylene carbonate, styrene, ethylene glycol, acrylic acid, acrylonitrile, methyl methacrylate, methyl acrylate, lauric acid, butyl acrylate and dioxolane. The above-mentioned organic monomers can be liquid at room temperature or when slightly heated, so these organic monomers can not only participate in the polymerization reaction as raw materials, but also can be used as solvents to disperse inorganic solid electrolytes, which can reduce the risk of adverse effects caused by the introduction of other solvents. Optionally, dioxolane includes 1,3-dioxolane. It should be noted here that, depending on the choice of organic monomer, in the polymerization reaction process, a single organic monomer can be used for polymerization, or two or more organic monomers can be used for copolymerization.
[0067] In some embodiments, in step S102, the content of the inorganic solid electrolyte in the coating slurry is 0.5wt% to 10wt%. The content of the inorganic solid electrolyte should not be too low, otherwise it is not conducive to the construction of a continuous lithium ion channel, and the content of the inorganic solid electrolyte does not need to be too high, because the inorganic solid electrolyte does not dissolve in the organic monomer. Too high a content of the inorganic solid electrolyte will affect the surface state of the coating layer, which is not conducive to improving the cycle performance of the solid-state battery. As an example, the content of the inorganic solid electrolyte in the coating slurry is 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt% or 10wt%.
[0068] In some embodiments, in step S102, the inorganic solid electrolyte is nanoscale inorganic solid electrolyte particles. Nanoscale inorganic solid electrolyte particles refer to inorganic solid electrolyte particles having a particle size of nanometers. Nanoscale inorganic solid electrolyte particles dispersed in an organic polymer can effectively construct abundant lithium ion channels, thereby improving the cycling performance of solid-state batteries.
[0069] In some embodiments, in step S102, the coating slurry further comprises a dispersant. The addition of the dispersant can promote uniform dispersion of the inorganic solid electrolyte in the organic monomer. In particular, when the inorganic solid electrolyte is nanoscale inorganic solid electrolyte particles, the dispersant can reduce the risk of agglomeration of the inorganic solid electrolyte particles. Optionally, the dispersant includes at least one of polyethylene glycol, polypropylene glycol, octylphenol polyoxyethylene ether, polysorbate monooleate, and polyvinyl pyrrolidone.
[0070] In some embodiments, in step S103, the reaction conditions of the polymerization reaction include: stirring at a first temperature for a first time, the first temperature is 25°C to 80°C, and the first time is 2h to 72h. In the preparation method of the positive electrode material, if the first temperature is too low, the reaction will be too slow, and if the first temperature is too high, the coating layer will be too thick and the density will decrease, and if the first temperature is too high, it will not be conducive to maintaining the stability of the material itself. As an example, the first temperature is 25°C, 35°C, 45°C, 55°C, 65°C, 75°C or 80°C. If the first time is too short, the coating layer will be too thin and the coating quality will be poor, and if the first time is too long, the coating layer will be too thick, which is not conducive to lithium ion transmission. As an example, the first time is 12h, 15h, 20h, 30h, 40h, 50h, 60h, 70h or 72h.
[0071] In some embodiments, in step S103, the first temperature is 35°C to 55°C, and the first duration is 2h to 48h. Appropriately increasing the first temperature and shortening the first duration can improve efficiency while ensuring the quality of the coating layer. As an example, the first temperature is 35°C, 37°C, 39°C, 41°C, 43°C, 45°C, 47°C, 49°C, 51°C, 53°C or 55°C; the first duration is 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h or 48h.
[0072] In some embodiments, in step S103, dispersing the first mixed material in the coating slurry includes: mixing the first mixed material and the coating slurry in a mass ratio of (20-55):(45-80) to obtain a mixed slurry, and then adding an organic monomer to adjust the solid content of the mixed slurry to 20wt% to 60wt%. As an example, the mass ratio of the first mixed material to the coating slurry is 20:80, 55:45, or 45:55. As an example, after the organic monomer is added, the solid content of the mixed slurry is 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, or 60wt%.
[0073] In some embodiments, before obtaining the positive electrode material in step S103, the method for preparing the positive electrode material further includes filtering, washing, drying, and grinding the polymerization reaction product. For example, the polymerization reaction product is washed with an organic monomer in a filtration device, and after washing, is dried in a forced air drying oven at 50°C to 60°C for 2 to 4 hours to remove residual organic monomer. The product is then ground to loosen agglomerated particles, and then dried in a vacuum drying oven at 100°C to 130°C for 10 to 15 hours.
[0074] In a third aspect, an embodiment of the present application provides a positive electrode sheet, comprising a current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode material as described above or a positive electrode material prepared by the method for preparing the positive electrode material as described above.
[0075] Since the positive electrode plate provided in the embodiment of the present application adopts the above-mentioned positive electrode material, the positive electrode plate has all the beneficial effects of the above-mentioned positive electrode material, which will not be described in detail here.
[0076] In some embodiments, the positive electrode active material layer further includes a conductive agent. The addition of a conductive agent can enhance the conductivity within the positive electrode active material layer. Optionally, the conductive agent includes at least one of vapor-grown carbon fiber, graphene, and conductive carbon black. As an example, the conductive agent includes vapor-grown carbon fiber. Vapor-Grown Carbon Fiber (VGCF) is a high-performance carbon fiber material prepared by chemical vapor deposition technology. VGCF can form a more continuous and stable conductive network, thereby reducing the internal resistance of the positive electrode sheet. As an example, the conductive carbon black includes Super P (SP for short).
[0077] In some embodiments, the positive electrode active material layer further includes a binder. The binder can bond the positive electrode materials together. As an example, the binder includes polytetrafluoroethylene (PTFE). PTFE can be fibrillated under the action of shear force, thereby bonding the components together. This eliminates the need for solvents during the preparation of the positive electrode sheet, thereby ensuring the compactness of the positive electrode active material layer and improving the solid-solid interface contact effect within the positive electrode active material layer.
[0078] In a fourth aspect, an embodiment of the present application provides a method for preparing a positive electrode sheet, comprising:
[0079] S201. Providing a dry material, where the dry material includes a positive electrode material, and the positive electrode material is the positive electrode material as described above or a positive electrode material prepared by the method for preparing the positive electrode material as described above;
[0080] S202, stirring and roller-pressing the dry material in sequence to obtain a positive electrode active material layer;
[0081] S203, rolling the positive electrode active material layer to the surface of the current collector to obtain a positive electrode sheet.
[0082] The positive electrode sheet prepared by the preparation method of the positive electrode sheet provided in the embodiment of the present application adopts the above-mentioned positive electrode material, and the positive electrode sheet has all the beneficial effects of the above-mentioned positive electrode material, which will not be described in detail here.
[0083] In some embodiments, the dry material further includes a binder and a conductive agent, the binder includes polytetrafluoroethylene, and the stirring process includes: the dry material is stirred at 80°C to 120°C at a stirring speed of 1200rpm to 2500rpm for 0.5min to 5min. During the stirring process, by controlling the temperature and stirring speed, especially the stirring speed, the polytetrafluoroethylene can be fiberized under the action of shear force, and the polytetrafluoroethylene particles can build a uniform self-supporting network among other components after fiberization. As an example, during the stirring process, the temperature of the dry material is 80°C, 90°C, 100°C, 110°C or 120°C; the stirring speed is 1200rpm, 1400rpm, 1600rpm, 1800rpm, 2000rpm, 2200rpm, 2400rpm or 2500rpm; and the stirring time is 0.5min, 1.0min, 2.0min, 3.0min, 4.0min or 5.0min.
[0084] In some embodiments, the roller pressing process includes vertical roller pressing and horizontal roller pressing, the temperature of vertical roller pressing is 100℃~200℃, the roller spacing is 20μm~50μm, and the pressure is 5t~20t, and the roller spacing of horizontal roller pressing is 20μm~50μm, and the pressure is 5t~20t. The roller pressing process can densify the positive electrode active material layer and further improve the solid-solid interface contact effect of the positive electrode material in the positive electrode active material layer. As an example, during the vertical roller pressing process, the temperature is 100℃, 120℃, 140℃, 160℃, 180℃ or 200℃, the roller spacing is 20μm, 25μm, 30μm, 35μm, 40μm, 45μm or 50μm, and the pressure is 5t, 10t, 15t or 20t. During the horizontal rolling process, the roller spacing is 20μm, 25μm, 30μm, 35μm, 40μm, 45μm or 50μm, and the pressure is 5t, 10t, 15t or 20t.
[0085] In a fifth aspect, an embodiment of the present application provides a solid-state battery, comprising a positive electrode sheet, a negative electrode sheet, and a solid electrolyte membrane arranged between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet as described above or the positive electrode sheet prepared by the preparation method of the positive electrode sheet as described above.
[0086] The solid-state battery provided in the embodiment of the present application includes the above-mentioned positive electrode material. The solid-state battery has all the beneficial effects of the above-mentioned positive electrode material, which will not be described in detail here.
[0087] In some embodiments, the solid electrolyte membrane comprises at least one of a halide electrolyte membrane, an oxide electrolyte membrane, a polymer electrolyte membrane, and a sulfide electrolyte membrane. Alternatively, the solid electrolyte membrane comprises a halide electrolyte membrane or a sulfide electrolyte membrane.
[0088] As an example, solid-state batteries are all-solid-state batteries. By using a solid electrolyte instead of a liquid electrolyte, all-solid-state batteries combine the positive electrode sheet, the negative electrode sheet, and the electrolyte membrane into a single structure. During charging and discharging, lithium ions migrate through the solid electrolyte, converting electrical energy into chemical energy. All-solid-state batteries not only improve battery safety but also significantly increase energy density and cycle life.
[0089] The following describes the method in conjunction with specific embodiments.
[0090] Example 1
[0091] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0092] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 0.5:99.5, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0093] S12, Polymerization Reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm. Mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0094] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material, that is, the surface of the high-nickel positive electrode active material is coated with a coating layer.
[0095] Example 2
[0096] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0097] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0098] S12, Polymerization Reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm. Mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0099] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0100] Example 3
[0101] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0102] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 3.0:97.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0103] S12, Polymerization Reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm. Mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0104] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0105] Example 4
[0106] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0107] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0108] S12, Polymerization Reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm. Mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 25°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0109] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0110] Example 5
[0111] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0112] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0113] S12, Polymerization Reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm. Mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 80°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0114] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0115] Example 6
[0116] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0117] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0118] S12, Polymerization Reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 4500ppm. Mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0119] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0120] Example 7
[0121] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0122] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0123] S12, polymerization reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 9000ppm, and mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0124] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0125] Example 8
[0126] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0127] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0128] S12, polymerization reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm, and mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 12 hours to obtain a preliminarily coated positive electrode material.
[0129] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0130] Example 9
[0131] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0132] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0133] S12, polymerization reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm, and mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 72 hours to obtain a preliminarily coated positive electrode material.
[0134] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0135] Example 10
[0136] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0137] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0138] S12, Polymerization Reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm. Mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 20:80 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 20wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0139] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0140] Example 11
[0141] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0142] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0143] S12, Polymerization Reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm. Mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 55:45 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 55wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0144] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0145] Example 12
[0146] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0147] S11. Prepare coating slurry: Mix and homogenize nano-oxide electrolyte powder (LATP) and polymerizable organic monomer (vinylene carbonate) in a mass ratio of 1.0:99.0. The slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0148] S12, polymerization reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm, and mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add organic monomer (vinylene carbonate) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0149] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (vinylene carbonate) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0150] Example 13
[0151] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0152] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (ethylene ethylene carbonate) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0153] S12, polymerization reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm, and mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add organic monomer (ethylene carbonate) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0154] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (ethylene carbonate) used in step S1; the product after washing is baked in a blast drying oven at 60°C for 2h, ground every 30min to disperse the agglomerated particles, and then baked in a vacuum drying oven at 120°C for 12h to obtain the final coated positive electrode material.
[0155] Example 14
[0156] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0157] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 7.0:93.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0158] S12, Polymerization Reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm. Mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0159] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0160] Example 15
[0161] This embodiment provides a positive electrode material, and the preparation process of the positive electrode material includes:
[0162] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 10.0:90.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0163] S12, Polymerization Reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm. Mix the high-nickel positive electrode active material with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0164] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0165] Application Example 1
[0166] This application example provides a solid-state battery, the preparation process of which includes:
[0167] S21. Prepare the positive electrode sheet:
[0168] The positive electrode material prepared in Example 1 was mixed with a solid electrolyte (specifically LATP), a conductive agent (specifically VGCF) and a binder (specifically polytetrafluoroethylene) in a mass ratio of 82:12:2:4 to obtain a mixed material. The mixed material was stirred and dispersed at a temperature of 90°C and a super strong shear force of 4000 rpm for 2 minutes to fiberize the polytetrafluoroethylene particles and construct a uniform self-supporting network between the other components.
[0169] Next, the powder is rolled vertically at 120°C between two hot-pressing rollers with a gap of 50 μm. The vertical roller pressure is controlled at 5 tons. After vertical rolling, horizontal rolling is performed, maintaining a pressure of 8 tons to ensure a gap of 30 μm between the two horizontal rollers. This horizontal rolling process yields a composite positive electrode sheet, which is then rolled onto the current collector surface to form the positive electrode sheet.
[0170] S22. Prepare the negative electrode: the negative electrode is a lithium metal negative electrode.
[0171] S23. Preparation of solid electrolyte membrane: Mix the solid electrolyte LATP:PTFE at a mass ratio of 98:2 at low speed, shear the evenly mixed powder at 2500 rpm for 2 minutes at 25°C to fibrillate the PTFE, and perform multi-stage roller pressing on the powder after high-speed shearing at 90°C for fiberization with a roller pressing pressure of 4t. The thickness of the electrolyte membrane after rolling is controlled to be 50μm.
[0172] S24. Assembly of all-solid-state soft-pack batteries: The prepared solid electrolyte membrane and the positive electrode sheets obtained after calendering are stacked and passed through a roller to ensure a close fit between the solid electrolyte membrane and the positive electrode sheets. The roller diameter is 30 mm, the roller temperature is 45°C, the roller speed is 4 rpm, and the roller gap is 20 μm. This results in a bonded electrolyte positive electrode composite layer. The bonded electrolyte positive electrode composite layer is die-cut into 56 mm × 69 mm rectangular sheets, the 20 μm thick solid electrolyte membrane is die-cut into 56 mm × 69 mm rectangular sheets, and the 30 μm thick lithium metal strip is die-cut into 55 mm × 68 mm rectangular sheets. The die-cutting pressure is 10 kPa, and the holding time is 4 seconds. The electrolyte positive electrode composite layer sheets and lithium sheets are alternately stacked in this order. Each stack is pressed with an axial pressure of 2 MPa for 10 seconds. The stacking is repeated three times in the order of composite layer-lithium sheet. The stacked single-layer soft-pack positive and negative electrodes are separated using the electrolyte membrane to perform single-layer soft-pack stacking. Under an argon atmosphere, the stacked layers of lead-out tabs were encapsulated with 135μm-thick aluminum-plastic film at a temperature of 180°C. The soft-pack battery was then hot-pressed at 60°C, with a pressure of 2MPa and a holding time of 10s. After hot-pressing, the soft-pack battery was allowed to rest for 6 hours, then cold-pressed at 4MPa for 30 seconds. After cold-pressing, the soft-pack battery was allowed to rest for 24 hours to obtain the final all-solid-state soft-pack battery.
[0173] Application Example 2
[0174] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in the manufacturing of the positive electrode plate in this application example is the positive electrode material provided in Example 2. Other aspects are the same as those in Application Example 1.
[0175] Application Example 3
[0176] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in the manufacturing of the positive electrode sheet in this application example is the positive electrode material provided in Example 3. Other aspects are the same as those in Application Example 1.
[0177] Application Example 4
[0178] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in the manufacturing of the positive electrode plate in this application example is the positive electrode material provided in Example 4. Other aspects are the same as those in Application Example 1.
[0179] Application Example 5
[0180] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in preparing the positive electrode sheet in this application example is the positive electrode material provided in Example 5. Other aspects are the same as those in Application Example 1.
[0181] Application Example 6
[0182] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in preparing the positive electrode sheet in this application example is the positive electrode material provided in Example 6. Other aspects are the same as those in Application Example 1.
[0183] Application Example 7
[0184] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in preparing the positive electrode sheet in this application example is the positive electrode material provided in Example 7. Other aspects are the same as those in Application Example 1.
[0185] Application Example 8
[0186] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in preparing the positive electrode sheet in this application example is the positive electrode material provided in Example 8. Other aspects are the same as those in Application Example 1.
[0187] Application Example 9
[0188] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in preparing the positive electrode plate in this application example is the positive electrode material provided in Example 9. Other aspects are the same as those in Application Example 1.
[0189] Application Example 10
[0190] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in the manufacturing of the positive electrode plate in this application example is the positive electrode material provided in Example 10. Other aspects are the same as those in Application Example 1.
[0191] Application Example 11
[0192] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in preparing the positive electrode plate in this application example is the positive electrode material provided in Example 11. Other aspects are the same as those in Application Example 1.
[0193] Application Example 12
[0194] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in the manufacturing of the positive electrode plate in this application example is the positive electrode material provided in Example 12. Other aspects are the same as those in Application Example 1.
[0195] Application Example 13
[0196] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in the manufacturing of the positive electrode plate in this application example is the positive electrode material provided in Example 13. Other aspects are the same as those in Application Example 1.
[0197] Application Example 14
[0198] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in the manufacturing of the positive electrode plate in this application example is the positive electrode material provided in Example 14. Other aspects are the same as those in Application Example 1.
[0199] Application Example 15
[0200] This application example provides a solid-state battery. The manufacturing process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in the manufacturing of the positive electrode plate in this application example is the positive electrode material provided in Example 15. Other aspects are the same as those in Application Example 1.
[0201] Comparative Example 1
[0202] This comparative example provides a solid-state battery. The preparation process of this solid-state battery differs from that of the solid-state battery in Application Example 1 in that the positive electrode material used in this comparative example to prepare the positive electrode plate is an uncoated high-nickel positive electrode active material (NCM811). Other processes are the same as in Application Example 1.
[0203] Comparative Example 2
[0204] This comparative example provides a solid-state battery. The difference between the preparation process of the solid-state battery and the preparation process of the solid-state battery in Application Example 1 is that:
[0205] The positive electrode material used in preparing the positive electrode plate in this comparative example is a high-nickel positive electrode active material (NCM811) coated only with a nano-sized oxide electrolyte powder (LATP). Specifically, the preparation process of this positive electrode material is as follows: the high-nickel positive electrode material and the oxide electrolyte powder are uniformly mixed in a certain ratio, specifically NCM811:LATP = 98:2 (mass ratio), p-xylene is added as a solvent (solid content 30wt%), and the sample is ball-milled in a planetary ball mill at 500rpm for 2h. The ball-milled sample is then dried to obtain the LATP-coated NCM material.
[0206] Other aspects are the same as those in Application Example 1.
[0207] Comparative Example 3
[0208] This comparative example provides a solid-state battery. The difference between the preparation process of the solid-state battery and the preparation process of the solid-state battery in Application Example 1 is that:
[0209] The positive electrode material used in the preparation of the positive electrode plate in this comparative example is a high-nickel positive electrode active material (NCM811) coated only with an organic polymer.
[0210] Specifically, the preparation process of the positive electrode material is as follows: providing a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm, mixing the high-nickel positive electrode active material with a polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 45:55 to obtain a mixed slurry. The organic monomer (1,3-dioxolane) is further added to adjust the solid content of the mixed slurry to 45wt%. The temperature of the mixed slurry is controlled at 45°C, and the mixed slurry is stirred for 24 hours to obtain a preliminary coated positive electrode material. The mixed slurry obtained after the above steps is repeatedly washed 5 times using suction filtration, and the washing liquid used is an organic monomer (1,3-dioxolane); the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0211] Other aspects are the same as those in Application Example 1.
[0212] Comparative Example 4
[0213] This comparative example provides a solid-state battery. The difference between the preparation process of the solid-state battery and the preparation process of the solid-state battery in Application Example 1 is that:
[0214] The positive electrode material used in the preparation of the positive electrode plate in this comparative example is a high-nickel positive electrode active material (NCM811) coated only with an organic polymer.
[0215] Specifically, the preparation process of the positive electrode material is as follows: providing a high-nickel positive electrode active material (NCM811) with a surface residual alkali amount of 3000ppm; providing a coating slurry, the coating slurry comprising a mixture of a solvent and a polymerizable organic monomer (ethylene carbonate), wherein the solvent comprises a chain organic solvent DME (dimethyl ether) and a cyclic organic solvent DOL (dioxolane) with a volume ratio of 1:1, and the concentration of the polymerizable organic monomer in the coating slurry is 1.5mol / L. The high-nickel positive electrode active material is mixed with according to a mass ratio of 45:55 to obtain a mixed slurry. The temperature of the mixed slurry is controlled to 45°C, and the mixed slurry is stirred for 24h to obtain a preliminarily coated positive electrode material. The mixed slurry obtained after the above steps was repeatedly washed 5 times by filtration, and the washing liquid used was an organic monomer (ethylene carbonate); the product after washing was baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0216] Other aspects are the same as those in Application Example 1.
[0217] Comparative Example 5
[0218] This comparative example provides a solid-state battery. The difference between the preparation process of the solid-state battery and the preparation process of the solid-state battery in Application Example 1 is that:
[0219] The preparation process of the positive electrode material used in preparing the positive electrode plate in this comparative example includes:
[0220] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0221] S12, polymerization reaction: Provide a high nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm and polytetrafluoroethylene (PTFE), mix NCM811 and PTFE in a ratio of 43:2 to form a first mixture; then homogenize the first mixture with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0222] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0223] Other aspects are the same as those in Application Example 1.
[0224] Comparative Example 6
[0225] This comparative example provides a solid-state battery. The difference between the preparation process of the solid-state battery and the preparation process of the solid-state battery in Application Example 1 is that:
[0226] The preparation process of the positive electrode material used in preparing the positive electrode plate in this comparative example includes:
[0227] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0228] S12, polymerization reaction: Provide a high-nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm and a conductive agent (SP). Mix NCM811 and SP in a ratio of 44:1 to form a first mixture; then homogenize the first mixture with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0229] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0230] Other aspects are the same as those in Application Example 1.
[0231] Comparative Example 7
[0232] This comparative example provides a solid-state battery. The difference between the preparation process of the solid-state battery and the preparation process of the solid-state battery in Application Example 1 is that:
[0233] The preparation process of the positive electrode material used in preparing the positive electrode plate in this comparative example includes:
[0234] S11. Prepare coating slurry: Take nano-scale oxide electrolyte powder (LATP) and polymerizable organic monomer (1,3-dioxolane) in a mass ratio of 1.0:99.0, mix and slurry, and the slurry is milky white and turbid, with no upper and lower stratification and no granularity, to obtain coating slurry.
[0235] S12, polymerization reaction: Provide a high nickel positive electrode active material (NCM811) with a surface residual alkali content of 3000ppm, a conductive agent (SP), and polytetrafluoroethylene (PTFE). Mix NCM811, SP, and PTFE in a ratio of 41:1:2 to form a first mixture; then homogenize the first mixture with the above-mentioned coating slurry in a mass ratio of 45:55 to obtain a mixed slurry. Continue to add an organic monomer (1,3-dioxolane) to adjust the solid content of the mixed slurry to 45wt%. Control the temperature of the mixed slurry to 45°C and stir the mixed slurry for 24 hours to obtain a preliminarily coated positive electrode material.
[0236] S13, washing and post-treatment: The mixed slurry obtained after step S2 is repeatedly washed 5 times by suction filtration, and the washing liquid used is the organic monomer (1,3-dioxolane) used in step S1; the product after washing is baked at 60°C in a forced air drying oven for 2 hours, ground every 30 minutes to disperse the agglomerated particles, and then baked at 120°C in a vacuum drying oven for 12 hours to obtain the final coated positive electrode material.
[0237] Other aspects are the same as those in Application Example 1.
[0238] Performance Characterization
[0239] 1. Scanning electron microscopy (SEM) was used to observe the micromorphology of the high nickel positive electrode active material (NCM811) before and after coating in Example 1. The results are as follows: Figure 1 and Figure 2 shown. Figure 1 is the SEM image of the high nickel positive electrode active material (i.e. the positive electrode active material) before coating. Figure 2 The SEM image of the high-nickel positive electrode active material (i.e., the positive electrode material) after coating is shown. After comparison, it is found that the particle size of the high-nickel positive electrode active material before and after coating is similar. This is because the coating layer coated on the surface of the high-nickel positive electrode active material is relatively thin. However, the high-nickel positive electrode active material before coating shows the characteristics of uniform particles and loose distribution. In comparison, the high-nickel positive electrode active material before and after coating shows a certain agglomeration phenomenon. This may be because after the organic monomer is polymerized into an organic polymer, the organic polymer is cross-linked together, causing the high-nickel positive electrode active material after coating to stick together.
[0240] 2. The positive electrode materials finally prepared in Example 2, Example 5 and Example 7 were subjected to thermogravimetric analysis (TGA). The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the change patterns of the thermal gravimetric curves of the positive electrode materials prepared in the three embodiments are similar, and all show that as the temperature increases, the weight retention rate of the material decreases. This is because as the temperature increases, the coating layer on the surface of the high-nickel positive electrode active material will undergo thermal decomposition, especially the organic polymer in the coating layer, which causes the weight retention rate of the material to decrease. However, the heights of the thermal gravimetric curves of different embodiments are different, among which the thermal gravimetric curve of Example 2 is the highest among the three, that is, the weight retention rate of the positive electrode material of Example 2 is the highest, indicating that the mass proportion of the coating layer in Example 2 is the lowest among the three; the thermal gravimetric curve of Example 5 is the lowest among the three, that is, the weight retention rate of the positive electrode material of Example 5 is the lowest, indicating that the mass proportion of the coating layer in Example 5 is the highest among the three; the thermal gravimetric curve of Example 7 is the middle one among the three, indicating that the mass proportion of the coating layer in Example 7 is also the middle one among the three. That is to say, on the surface of the high-nickel positive electrode active material with the same particle size, the thickness of the coating layer in Example 2 is the smallest, the thickness of the coating layer in Example 7 is the second largest, and the thickness of the coating layer in Example 5 is the largest.
[0241] Further comparison of the preparation processes of Example 2, Example 5 and Example 7 shows that the difference between Example 2 and Example 5 is that the temperature of the polymerization reaction is different, wherein the temperature of Example 2 is 45°C, while the temperature of Example 5 is 80°C. This shows that as the temperature of the polymerization reaction increases, the polymerization reaction of the organic monomer can be promoted, thereby increasing the thickness of the coating layer. The difference between Example 2 and Example 7 is that the amount of residual alkali on the surface of the high-nickel positive electrode active material is different, wherein the amount of residual alkali in Example 2 is 3000ppm, while the amount of residual alkali in Example 7 is 9000ppm. This shows that the residual alkali acts as an initiator, and increasing the amount of residual alkali (i.e., the residual alkali amount) can promote the polymerization reaction of the organic monomer, thereby increasing the thickness of the coating layer.
[0242] In addition, the thickness of the coating layer in the positive electrode material provided in each embodiment was calculated by thermogravimetric analysis, and it was found that the thickness of the coating layer was 8 nm to 20 nm.
[0243] 3. The components of the coating layer in the cathode materials finally prepared in Example 2, Example 4, Example 6, Example 8 and Example 10 were analyzed using a Fourier transform infrared spectroscopy (FT-IR) instrument. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the characteristic peak positions of the Fourier transform infrared spectra of the five embodiments are basically consistent: mainly including CH (1342cm -1)、CO(1238cm -1 ), symmetrical COC (1145cm -1 ), asymmetric COC (1064cm -1 )、CC(1133cm -1 ). This shows that the components of the coating layer in the positive electrode materials finally prepared in the five embodiments are basically the same. Further comparison of the five embodiments shows that the solid electrolyte, organic monomer and positive electrode active material used in the five embodiments are the same. The differences lie in the content of the solid electrolyte, the temperature of the polymerization reaction, the amount of initiator used, the polymerization reaction time, and the mass ratio of the first mixture to the coating slurry. These differences mainly lead to changes in the thickness of the coating layer and have little effect on the composition of the coating layer.
[0244] 4. The solid-state batteries prepared in each application example and each comparative example were subjected to a cycle performance test, specifically a capacity retention test. The test process was as follows: at 25°C, the solid-state battery was cycled 100 times with a test voltage of 2.75V to 4.35V, an activation current of 0.1C, and a cycle current of 0.33C; the capacity retention rate was calculated by dividing the capacity after 100 cycles by the initial capacity to obtain the capacity retention rate after the cycle. The test results are recorded in Table 1.
[0245] Table 1
[0246]
[0247]
[0248] The difference between the solid-state batteries prepared in each application example and each comparative example lies in the different positive electrode materials used. For the preparation conditions of each positive electrode material, please refer to Table 1 and the corresponding preparation examples.
[0249] Comparing Comparative Example 1 with Application Examples 1 to 13, it can be seen that the capacity retention rates of Application Examples 1 to 13 are significantly improved compared to Comparative Example 1, which shows that coating the surface of the positive electrode active material with a coating layer comprising an inorganic solid electrolyte and an organic polymer can effectively improve the cycle performance of the solid-state battery. On the one hand, the coating layer is coated on the surface of the positive electrode active material, and the inorganic solid electrolyte in the coating layer can form a good contact with the positive electrode active material. At the same time, the inorganic solid electrolyte with good ionic conductivity can also construct a "high-speed channel" for lithium ion transport in the positive electrode material, thereby effectively improving the solid-solid contact effect inside the positive electrode material, and the coating layer also has the ability to reduce the rate of interfacial chemistry and electrochemical reactions, which is beneficial to inhibiting the initiation and growth of metal dendrites and reducing the risk of short circuit in the solid-state battery; on the other hand, the organic polymer in the coating layer can make the coating layer have a certain ability to buffer and absorb strain, thereby reducing the adverse effects of the volume change of the interface material when the solid-state battery is working. Thanks to the above two aspects, the positive electrode active material coated with a coating layer containing an inorganic solid electrolyte and an organic polymer can take into account the requirements of the multi-physical field synergistic effect of the positive electrode interface of the solid-state battery, and promote the improvement of the cycle performance of the solid-state battery.
[0250] Comparing Application Examples 1 to 3 and Application Examples 14 and 15, it can be seen that when the addition amount of solid electrolyte (LATP) particles in the coating layer increases from 0.5wt% to 10.0wt%, the capacity retention rate of the solid-state battery shows a trend of first increasing and then decreasing. This is because as the content of the inorganic solid electrolyte increases, the ion conductivity of the coating layer is improved, and the cycle performance of the solid-state battery is improved. However, if the content of the inorganic solid electrolyte in the coating layer is too high, it may affect the state of the surface of the positive electrode material, and in turn affect the contact between the inorganic solid electrolytes, thereby reducing the cycle performance of the solid-state battery.
[0251] By comparing Application Example 2, Application Example 4 and Application Example 5, it can be seen that when the temperature of the polymerization reaction is increased from 25°C to 45°C, the capacity retention rate of the solid-state battery increases from 93.51% to 96.56%. When the temperature continues to rise to 80°C, the capacity retention rate of the solid-state battery decreases. This shows that appropriate temperature increase within a certain temperature range is conducive to forming a more stable coating layer and improving the coating quality of the coating layer on the positive electrode active material, while too high a temperature may destroy the coating effect of the coating layer. For example, too high a temperature may lead to the intensification of the polymerization reaction of the organic monomer, which in turn leads to a decrease in the density of the coating layer and an increase in the thickness. Not only will the coating effect of the coating layer on the active material deteriorate, but the performance of the coating layer in transporting lithium ions will also decrease.
[0252] Comparing Application Examples 2, 6, and 7, it can be seen that when the residual alkali content on the surface of the high-nickel positive electrode active material is increased from 3000ppm to 9000ppm, the capacity retention rate of the solid-state battery decreases from 96.56% to 62.57%. This is because the residual alkali content on the surface of the high-nickel positive electrode active material can regulate the thickness of the coating layer by controlling the rate of the polymerization reaction; as the residual alkali content increases, the coating layer thickness increases, which is not conducive to the transmission of lithium ions, thereby causing a decrease in the cycle performance of the solid-state battery and a decrease in the capacity retention rate; while a lower residual alkali content will form a more uniform coating layer at a more moderate rate, which is beneficial to the cycle stability of the positive electrode material interface.
[0253] Comparing Application Examples 2, 8, and 9, it can be seen that when the polymerization reaction time is increased from 12h to 24h, the capacity retention rate of the solid-state battery increases from 90.95% to 96.56%. When the polymerization reaction time is further increased to 72h, the capacity retention rate decreases. Generally, as the polymerization reaction time increases, the quality and stability of the coating layer improve, and the coating effect is improved. However, excessively long polymerization reaction time will form a thicker coating layer, which is not conducive to the transmission of lithium ions and instead leads to a decrease in the cycle performance of the solid-state battery.
[0254] Comparison of Application Examples 2, 10, and 11 shows that by adjusting the mass ratio of the first mixed material containing the positive electrode active material to the coating slurry containing the organic monomer, the capacity retention rate of the solid-state battery shows a fluctuating trend, but the actual fluctuation is small, only 4%. By comparison, it can be seen that the capacity retention rate of the solid-state battery is the highest when the mass ratio of the first mixed material to the coating slurry is 45:55.
[0255] By comparing Application Example 2, Application Example 12 and Application Example 13, it can be seen that when the polymerizable organic monomer is 1,3-dioxolane, the coating layer has better performance and the capacity retention rate of the solid-state battery is larger. When the polymerizable organic monomer is vinylene carbonate or vinyl ethylene carbonate, the effect is worse than 1,3-dioxolane.
[0256] By comparing Application Example 2, Comparative Example 2 and Comparative Example 3, and Comparative Example 13 and Comparative Example 4, it can be seen that compared with a coating layer of a single composition (containing only a solid electrolyte or an organic polymer), when the coating layer contains both an inorganic solid electrolyte and an organic polymer, the cycle performance of the solid-state battery is significantly improved. This is because the coating layer containing both an inorganic solid electrolyte and an organic polymer takes into account the composite effect of the inorganic conductor and the organic conductor, and has the ability to accommodate strain and reduce the rate of interfacial chemical and electrochemical side reactions. In addition, the inorganic solid electrolyte and the organic polymer cooperate with each other to enable the positive electrode material to take into account the requirements of the multi-physical field synergistic effect of the positive electrode interface of the solid-state battery, thereby promoting the improvement of the cycle performance of the solid-state battery.
[0257] Comparing Application Example 2, Comparative Example 5, and Comparative Example 7, it can be seen that in the process of forming the coating layer by liquid phase dispersion, the addition of the binder PTFE is not conducive to improving the cycle performance of the solid-state battery. Because if the coating layer contains a binder, it is equivalent to wrapping a layer of binder that is difficult to disperse evenly on the surface of the positive electrode active material particles. This highly viscous binder layer will have an adverse effect on the co-coating of LATP and 1,3-dioxolane, making it difficult to form an ideal coated intercalated ion network. This method makes it difficult to fiberize the granular PTFE in the coating layer and cannot form a uniform three-dimensional bonding network in space. In this way, it is difficult for the positive electrode material particles to be in close contact, exacerbating the deterioration of battery performance.
[0258] If the coating layer does not contain PTFE, it is easier to construct a composite coating layer from a technical point of view, which is conducive to constructing a more ideal positive electrode-electrolyte interface layer and inhibiting interfacial reactions.
[0259] Comparing Application Example 2, Comparative Example 6 and Comparative Example 7, it can be seen that in the process of forming the coating layer by liquid phase dispersion, the addition of the conductive agent SP is not conducive to improving the cycle performance of the solid-state battery. The conductive agent SP is added to 1,3-dioxolane containing LATP and NCM811, and mixed into the positive electrode coating layer by liquid phase dispersion. In fact, the addition of SP does not directly affect the progress of the coating reaction, but it can indirectly affect the uniformity of the coating layer by affecting the mixing uniformity of other solid phase components. Not only that, it is difficult to disperse SP evenly by liquid phase dispersion, and there may be local agglomeration, which is not conducive to constructing a uniform composite ion conductor coating layer on the surface of the positive electrode active material particles. Compared with Application Example 2, the effect is not ideal.
[0260] The above is a detailed introduction to the embodiments of the present application. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for those skilled in the art, based on the ideas of the present application, there may be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A positive electrode material, characterized in that The invention comprises a positive electrode active material and a coating layer coated on the surface of the positive electrode active material, wherein the coating layer comprises an organic polymer and an inorganic solid electrolyte dispersed in the organic polymer.
2. The positive electrode material according to claim 1, characterized in that The positive electrode active material includes at least one of a nickel-cobalt-manganese ternary material and a nickel-cobalt-aluminum ternary material; and / or, The inorganic solid electrolyte includes an oxide solid electrolyte, and the oxide solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, lithium lanthanum zirconate and tantalum-doped lithium lanthanum zirconate; and / or, The organic polymer is polymerized from at least one of the following organic monomers: vinylene carbonate, vinyl ethylene carbonate, styrene, ethylene glycol, acrylic acid, acrylonitrile, methyl methacrylate, methyl acrylate ketone, lauric acid, butyl acrylate, and dioxolane.
3. The positive electrode material according to claim 1, characterized in that The coating layer has a thickness of 8 nm to 20 nm; and / or the inorganic solid electrolyte is nanoscale inorganic solid electrolyte particles.
4. A method for preparing a positive electrode material, characterized in that: include: Providing a first mixed material, wherein the first mixed material includes a positive electrode active material and an initiator attached to a surface of the positive electrode active material; Providing a coating slurry, wherein the coating slurry includes a liquid organic monomer and an inorganic solid electrolyte dispersed in the organic monomer; The first mixed material is dispersed in the coating slurry, and the organic monomer undergoes a polymerization reaction under the action of the initiator to generate an organic polymer. The organic polymer and the inorganic solid electrolyte adhere to the surface of the positive electrode active material and form a coating layer, thereby obtaining a positive electrode material.
5. The method for preparing the positive electrode material according to claim 4, wherein: The positive electrode active material includes at least one of a nickel-cobalt-manganese ternary material and a nickel-cobalt-aluminum ternary material; and / or, The initiator includes an alkaline substance, and in the first mixture, the content of the alkaline substance on the surface of the positive electrode active material is less than or equal to 9000 ppm; and / or, The inorganic solid electrolyte includes an oxide solid electrolyte, and the oxide solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, lithium lanthanum zirconate and tantalum-doped lithium lanthanum zirconate; and / or, The organic monomer comprises at least one of vinylene carbonate, vinyl ethylene carbonate, styrene, ethylene glycol, acrylic acid, acrylonitrile, methyl methacrylate, methyl acrylate ketone, lauric acid, butyl acrylate and dioxolane; and / or, In the coating slurry, the content of the inorganic solid electrolyte is 0.5wt% to 10wt%; and / or, The inorganic solid electrolyte is nanoscale inorganic solid electrolyte particles; and / or, The coating slurry further comprises a dispersant, and the dispersant comprises at least one of polyethylene glycol, polypropylene glycol, octylphenol polyoxyethylene ether, polysorbate monooleate and polyvinyl pyrrolidone.
6. The method for preparing the positive electrode material according to claim 4, wherein: The reaction conditions of the polymerization reaction include: stirring at a first temperature for a first time, the first temperature is 25° C. to 80° C., and the first time is 2 hours to 72 hours; and / or, Dispersing the first mixed material in the coating slurry includes: mixing the first mixed material and the coating slurry in a mass ratio of (20-55):(45-80) to obtain a mixed slurry, and then adding the organic monomer to adjust the solid content of the mixed slurry to 20wt%-60wt%; and / or, Before obtaining the positive electrode material, the method for preparing the positive electrode material further comprises: filtering, washing, drying and grinding the product of the polymerization reaction.
7. A positive electrode plate, characterized in that: The invention comprises a current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode material according to any one of claims 1 to 3 or the positive electrode material prepared by the preparation method of the positive electrode material according to any one of claims 4 to 6.
8. The positive electrode sheet according to claim 7, characterized in that: The positive electrode active material layer further includes a binder, and the binder includes polytetrafluoroethylene; and / or the positive electrode active material layer further includes a conductive agent.
9. A method for preparing a positive electrode sheet, characterized in that: include: Providing a dry material, wherein the dry material includes a positive electrode material, wherein the positive electrode material is the positive electrode material according to any one of claims 1 to 3 or the positive electrode material prepared by the method for preparing the positive electrode material according to any one of claims 4 to 6; The dry material is sequentially subjected to stirring and roller pressing to obtain a positive electrode active material layer; The positive electrode active material layer is pressed onto the surface of the current collector to obtain a positive electrode sheet.
10. A solid-state battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane arranged between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet as described in claim 7 or 8 or the positive electrode sheet prepared by the preparation method of the positive electrode sheet as described in claim 9.